JENIS-JENIS KAPANG PENGONTAMINASI CABE GILING DARI BEBERAPA PASAR TRADISIOANAL DI KOTA PADANG - Subandini, Nani; Fifendy, Mades; Periadnadi, Periadnadi (Pendidikan Biologi, 2013)
ABSTRACT Ground  cayenne  pepper  is  one  of  the  preparations  that  are  sold  in  the  markets. Cayenne is one food that is often contaminated by soil, dirt and microorganisms. Contamination  can  occur  during  harvesting,  transport,  processing  and  marketing.  The purpose of this study to determine the types of molds contaminating ground pepper. This study uses purposive sampling method with mold growing on Potato Dextrose Agar media and create later identify pure culture. Results of this study are 5 types of molds are milled pepper pengkontaminsi Aspergillus ustus, Aspergillus niger, Aspergillus sp, Rhizopus stolonifer and Penicillium corylophilum.